2012
DOI: 10.1002/dev.21073
|View full text |Cite
|
Sign up to set email alerts
|

Hand preference for pointing and language development in toddlers

Abstract: The aim of this study was to investigate the relationship between hand preference for communicative gestures and language during development. Hand preference for pointing gestures and level of language were assessed in 46 toddlers between 12 and 30 months of age. Results showed a right-hand preference for pointing and the use of a developmental quotient (DQ) for language revealed a significant correlation between the degree of hand preference and DQ for language in children with a quotient above 100. Thus, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
20
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 56 publications
2
20
0
1
Order By: Relevance
“…Results implementing more traditional analyses of using correlations between hand preference and language found a similar pattern to previous longitudinal and cross-sectional research where monthly hand preference scores show tremendous fluctuation with respect to language (Bates et al, 1986;Cochet et al, 2011;Esseily et al, 2011;Ramsay, 1980Ramsay, , 1984Ramsay, , 1985Vauclair & Cochet, 2013 (Spencer et al, 2006;Thelen & Smith, 2006).…”
Section: Hand Preference Trajectories and Language Outcomessupporting
confidence: 81%
See 1 more Smart Citation
“…Results implementing more traditional analyses of using correlations between hand preference and language found a similar pattern to previous longitudinal and cross-sectional research where monthly hand preference scores show tremendous fluctuation with respect to language (Bates et al, 1986;Cochet et al, 2011;Esseily et al, 2011;Ramsay, 1980Ramsay, , 1984Ramsay, , 1985Vauclair & Cochet, 2013 (Spencer et al, 2006;Thelen & Smith, 2006).…”
Section: Hand Preference Trajectories and Language Outcomessupporting
confidence: 81%
“…A crucial factor in understanding how variability in hand use experience shapes language development is the implementation of longitudinal designs using a trajectory-based approach. However, a large portion of research examining the relations between early handedness and language has used cross-sectional designs or longitudinal designs with too few time points (Bates, O'Connell, Vaid, Sledge, & Oakes, 1986;Cochet, Jover, & Vauclair, 2011;Esseily, Jacquet, & Fagard, 2011;Ramsay, 1980Ramsay, , 1984Ramsay, , 1985Vauclair & Cochet, 2013). Such work has found a variety of shifts in hand use around times of significant change in language like the onset of duplicated syllable babbling, after the word spurt, or around the initial use of word combinations (e.g., Bates et al, 1986;Cochet et al, 2011;Ramsay, 1984).…”
Section: Handedness Trajectories and Languagementioning
confidence: 99%
“…A right-sided asymmetry especially for pointing gestures has been reported in several studies (Bates et al, 1986;Blake, O'Rourke, & Borzellino, 1994;Vauclair & Imbault, 2009;Young, Lock, & Service, 1985). Moreover, Esseily et al (2011) showed that right-handed infants for pointing understood and produced more words than non-right-handed infants, and Vauclair and Cochet (2010) observed a U-shaped relationship in toddlers between 12 and 30 months of age between the degree of hand preference for pointing and the developmental quotient for language. Results from the study by Bates et al (1986) also support the existence of a dynamic nonlinear relationship between speech and righthand use: these authors failed to reveal significant correlations between language score and handedness in pointing and symbolic gestures, whereas a nonlinear relationship was observed at 20 months of age.…”
Section: Handedness For Pointing and Language Developmentmentioning
confidence: 57%
“…As with other domains of motor development, would manual asymmetries, like hand preferences, influence cognitive development? Prior research has found that right hand use or right handedness predicts increased skill for motor actions (Larsen, Helder, & Behen, ), greater language ability (Esseily, Jacquet, & Fagard, ; Nelson, Campbell & Michel, ; Vauclair & Cochet, ) and greater cognitive abilities (Larsen, Helder, & Behen, ), while non‐right‐handedness was associated with language impairment (Hill & Bishop, ), and physical and mental health problems (e.g., prematurity: Domellöf, Johansson, & Rönnqvist, ; schizophrenia and schizotypy: Chen & Su, ; Hirnstein & Hugdahl, ). Greater frequency of right hand use has been connected to greater lateralization of language functions (Gonzalez & Goodale, ), especially language production (Esseily, Jacquet, & Fagard, ; Jacquet, Esseily, & Fagard, ).…”
Section: Introductionmentioning
confidence: 99%